Estudo do potencial de multigeração para unidades consumidoras residenciais e comerciais no Brasil - Delgado, Danielle Bandeira de Mello (2023)
With energy transition, the scenario for energy supply that is currently being built in the world is more decentralized, intelligent, with a clean model and that grants the final consumer more autonomy. Multigeneration technologies provide significant socioeconomic and environmental benefits related to the efficient use of energy resources, such as the reduction of operating costs and carbon emissions. The motivation of this study is to ensure that a wide range of energy end users in Brazil can take advantage of these systems, through lower production costs and application of advanced technologies in this area. The main objective of this work is to develop a flexible tool that is easy to use by end users for structural and parametric optimization of multigeneration systems for typical consumer units, with focus on minimizing costs. For the system modelling, all technical, financial and computational data were collected and a superstructure containing all energy resources and commercial equipment available was proposed. The linear programming was modeled with all possible configurations and the exhaustive search for the optimal system was performed. The optimization problem was implemented using the C++ language and solved using the ILOG CPLEX Optimization Studio solver by IBM. A residential and a commercial consumer were used as case studies, with their annual energy demands being raised based on specific methodologies and considering representative days. Were also included the demanded energy related to the recharge of electric vehicles in the residential consumer unit, the production of surplus electricity and the application of Law 14,300/2022, which establishes the legal framework for microgeneration and distributed minigeneration, the Energy Compensation System (SCEE), and the Social Renewable Energy Program (PERS) in Brazil. The optimization model determined the optimal combination of equipment, connections and energy sources within the superstructures planned for both residential and commercial units, allowing visualization of technologies and costs (hourly and monthly) configuration, in addition to the surplus electricity produced. As results presented for the residential center, the implementation of 102 photovoltaic modules and biomass boilers for hot water production stands out. The optimal system presented a 27.02% reduction in the total annual cost when compared to a reference system, but with an initial investment 41.69% higher. For the commercial center, the economic optimum included a biomass boiler, which contributed to a 48.37% reduction in electricity imported from the electrical grid, with a reduction in the initial investment in equipment, and even with a total annual cost lower by 19.38% compared to a reference system. By carrying out the sensitivity analyses, it was possible to verify the ease and flexibility of the implemented system, with dynamic simulations and quick results and, immediately, that the optimal system was more sensitive to the removal of boilers from biomass and presented a good performance in the face of variations in the utilities prices, maintaining its original configuration in most scenarios.